Perencanaan Strategis Dalam Mengelola Upaya Pencegahan Pencemaran Lingkungan di Dinas Lingkungan Hidup Kabupaten Nias Utara - Threesman Nazara; Eliagus Telaumbanua; Emanuel Zebua; Delipiter Lase (LPPM Universitas HKBP Nommensen, 2024)
The aim of this research is to analyze strategies for managing the prevention of environmental pollution in North Nias Regency. Then to identify the efforts made to prevent environmental pollution in North Nias Regency. The research method used by researchers is qualitative research. In this qualitative approach, researchers involved in-depth interviews with employees of the North Nias Regency Environmental Service office. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions. From the research results, it can be concluded that environmental pollution planning in North Nias Regency faces many problems. The absence of adequate resources, such as funds and skilled labor, to implement environmental pollution prevention programs is a major challenge